MARKETING STRATEGY TO INCREASE TOURIST VISITS ON NATURE TOURISM OF MEMPAWAH MANGROVE PARK IN THE PASIR VILLAGE OF MEMPAWAH REGENCY - Utin Nina Hermina (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2019)
Nature tourism is one of the tourism that is trending and loved both local and foreign tourists. It is expected to bring an impact on improving the region's economy, and the community around the tourist attractions can be actively involved in there. Mempawah Regency is one of the regencies in West Kalimantan, one of its natural attractions is "Mempawah Mangrove Park", a mangrove (Mangrove forest) tourist spot. The purpose of this research is to find a marketing strategy through the marketing mix of tourism products, promotions, and prices that can affect the increasing visiting of tourists who visit the natural tourism of Mangrove Park in the Pasir village of Mempawah Regency. The research method used surveys using questionnaires as the method of data retrieval. Samples selected with a non-probability sampling method of purposive sampling. The analytical tools used in this study were descriptive verification. Collecting the results of a questionnaire that was further emulated and scripted based on analysis and study of existing theories. The results of this research showed that the product in the mangrove tourism does not affect the tourists, and the promotion is not done because there is no special promotion from the related service or from the exhibition of tourism that presents information about the nature tourism of Mangrove Park, but for the price, they agree if the entrance price of the tour is to be said as per the facilities provided in the nature tourism.